Design of maintenance structures for rural electrification with solar home systems. The case of the Moroccan program. (15th December 2016) - Carrasco, L.M.; Martín-Campo, F.J.; Narvarte, L.; Ortuño, M.T.; Vitoriano, B.
Abstract: In decentralised rural electrification through solar home systems, private companies and promoting institutions are faced with the problem of deploying maintenance structures to operate and guarantee the service of the solar systems for long periods (ten years or more). The problems linked to decentralisation, such as the dispersion of dwellings, difficult access and maintenance needs, makes it an arduous task. This paper proposes an innovative design tool created ad hoc for photovoltaic rural electrification based on a real photovoltaic rural electrification program in Morocco as a special case study. The tool is developed from a mathematical model comprising a set of decision variables (location, transport, etc.) that must meet certain constraints and whose optimisation criterion is the minimum cost of the operation and maintenance activity assuming an established quality of service. The main output of the model is the overall cost of the maintenance structure. The best location for the local maintenance headquarters and warehouses in a given region is established, as are the number of maintenance technicians and vehicles required. Highlights: A mathematical optimisation model has been implemented with GAMS. The model is an ad-hoc tool for the design of maintenance structures in decentralised PVRE programmes. An objective function computing the cost of the O&M activities is optimised. A prototype model has been implemented and validated in two provinces of a real PVRE programme.